Prevalence, awareness, treatment and control of hypertension, diabetes and hypercholesterolemia, and associated risk factors in the Czech Republic, Russia, Poland and Lithuania: a cross-sectional study - Lu, Wentian; Pikhart, Hynek; Tamosiunas, Abdonas; Kubinova, Ruzena; Capkova, Nadezda; Malyutina, Sofia; Pająk, Andrzej; Bobak, Martin (BMC public health, 2022)
BACKGROUND: Empirical evidence on the epidemiology of hypertension, diabetes and hypercholesterolemia is limited in many countries in Central and Eastern Europe. We aimed to estimate the prevalence, awareness, treatment and control of hypertension, diabetes and hypercholesterolemia in the Czech Republic, Russia, Poland and Lithuania, and to identify the risk factors for the three chronic conditions. METHODS: We analysed cross-sectional data from the HAPIEE study, including adults aged 45-69 years in the Czech Republic, Russia, Poland and Lithuania, collected between 2002 and 2008 (total sample N = 30,882). Among prevalent cases, we estimated awareness, treatment, and control of hypertension, diabetes and hypercholesterolemia by gender and country. Multivariate logistic regression was applied to identify associated risk factors. RESULTS: In each country among both men and women, we found high prevalence but low control of hypertension, diabetes, and hypercholesterolemia. Awareness rates of hypertension were the lowest in both men (61.40%) and women (69.21%) in the Czech Republic, while awareness rates of hypercholesterolemia were the highest in both men (46.51%) and women (51.20%) in Poland. Polish participants also had the highest rates of awareness (77.37% in men and 79.53% in women), treatment (71.99% in men and 74.87% in women) and control (30.98% in men and 38.08% in women) of diabetes. The common risk factors for the three chronic conditions were age, gender, education, obesity and alcohol consumption. CONCLUSIONS: Patterns of awareness, treatment and control rates of hypertension, diabetes and hypercholesterolemia differed by country. Efforts should be made in all four countries to control these conditions, including implementation of international guidelines in everyday practice to improve detection and effective management of these conditions.
Keywords: rizikové faktory; Diabetes Mellitus; Litva; diabetes mellitus; Male; Female; Hypercholesterolemia; Dyslipidemia; Česká republika; Central and Eastern Europe; průřezové studie; Polsko; Russia; mužské pohlaví; hypertenze; ženské pohlaví; Adult; Risk Factors; Czech Republic; Lithuania; Blood pressure; Total cholesterol; hypercholesterolemie; dospělí; Cross-Sectional Studies; Rusko; Fasting plasma glucose; Prevalence; lidé; Humans; Hypertension; prevalence; Poland